Photoinduced energy and electron transfer processes in hexapyropheophorbide a-fullerene [C60] molecular systems - Regehly, Martin; Ermilov, Eugeny; Helmreich, Matthias; Hirsch, Andreas; Jux, Norbert; Röder, Beate (Journal of Physical Chemistry B, 2007)
The photophysical properties of the novel hexapyropheophorbide a (P6), and hexakis (pyropheophorbide a)-C6o (FP6) were studied and compared with those of hexakis (pyropheophorbide a)-fullerene [5:1] hexaadduct (FHP6). It was found that after light absorption the pyropheophorbide a molecules in all three compounds undergo very efficient energy transfer as well as partly excitonic interactions. The last process results in the formation of energy traps, which could be resolved experimentally. For P6, due to shorter distances between neighboring dye molecules, stronger interactions between pyropheophorbide a units than for FHP6 were observed. As a consequence, the excitation energy is delivered rapidly to traps formed by stacked pyropheophorbide a molecules resulting in the reduction of fluorescence, intersystem crossing, and singlet oxygen quantum yields compared to the values of FHP6. For FP6 the reduction of these values is much stronger due to an additional fast and efficient deactivation process, namely photoinduced electron transfer from pyropheophorbide a to the fullerene moiety. Consequently, FP6 can be considered as a combination of a light-harvesting system consisting of several separate pyropheophorbide a molecules and a charge-separating center. © 2007 American Chemical Society.